Cocoa Diet and Antibody Immune Response in Preclinical Studies - Camps-Bossacoma, Mariona; Massot-Cladera, Malen; Abril-Gil, Mar; Franch, Angels; Pérez-Cano, Francisco J.; Castell, Margarida (Frontiers in Nutrition, 2017)
The ability of cocoa to interact with the immune system in vitro and in vivo has been described. In the latter context, a cocoa-enriched diet in healthy rats was able to modify the immune system’s functionality. This fact could be observed in the composition and functionality of lymphoid tissues such as the thymus, spleen and lymph nodes. Consequently, immune effector mechanisms such as antibody synthesis were modified. A cocoa-enriched diet in young rats was able to attenuate the serum levels of immunoglobulin G (IgG), IgM and IgA and also the intestinal IgM and IgA secretion. Moreover, in immunized rats, the intake of cocoa decreased specific IgG1, IgG2a, IgG2c and IgM concentrations in serum. This immune-regulator potential was then tested in disease models in which antibodies play a pathogenic role. A cocoa-enriched diet was able to partially prevent the synthesis of autoantibodies in a model of autoimmune arthritis in rats and was also able to protect against IgE and T helper 2-related antibody synthesis in two rat models of allergy. Likewise, a cocoa-enriched diet prevented an oral sensitization process in young rats. In this review, we will focus on the influence of cocoa on the acquired branch of the immune function. Therefore, we will focus on how a cocoa diet influences lymphocyte function both in the systemic and intestinal immune system. Likewise, its potential role in preventing some antibody-induced immune diseases is also included. Although further studies must characterize the particular cocoa components responsible for such effects, and nutritional studies in humans need to be carried out, cocoa has potential as a nutraceutical agent in some hypersensitivity status.